At the Crossroads of Christology - Webb, Stephen H. (Toronto journal of theology, 1994)
Well, let me say I knew that sooner or later a "real" Barthian would read my book, and it would not be pretty. Since my book is about rhetoric, as well as Barth, let me make a comment or two about its context. It was not written for Barth scholars (a title I would not claim for myself); in fact, it was not written (University of Chicago Divinity School) where Barth was much read or taken seriously at all. It was written as a way of putting Barth into conversation with a lot of people who could benefit, I thought, from his voice. I saw certain parallels between Barth's early theology and many of the issues and claims of post-modem literary theorists, philosophers and rhetoricians, and I wanted to draw Barth into that conversation. (My role models in this, by the way, were Robert Scharlemann and Walter Lowe.) I also thought that many of the recent advances in rhetorical theory could be applied to a great theological writer with productive results. I was glad to write this book at an institution where the blurring of boundaries was encouraged and celebrated.